The effect of imipramine on the behavior of albino mice in presence of selenium - S Aburawi; S Baayo (Libyan International Medical University Journal)
Introduction: Imipramine, a tricyclic antidepressant used in the treatment of depression, anxiety, and other mental condition. Selenium is useful in managing depression and anxiety. Aim: The present study was aimed to investigate the behavior effects of imipramine in presence of selenium on anxiety, spontaneous motor activity and antidepressant behavior. Methods: Mice were divided into 5 groups of six each. Group 1 (control) was given 5ml/kg 1% Tween 80.Group 2 was given selenium (200 μg/kg). Group 3 was given diazepam (1 mg/kg).Group 4 mice was given imipramine (10 mg/kg).Group 5 was given combined treatment of selenium and imipramine. All drugs were injected as sub-acute (three doses), intraperitoneally and administered at 24, 5, and 1.0 hours before scoring. Animals were tested in the elevated plus maze, open field and forced swim test one hour after drugs injections. All drugs were given by intraperitoneal route. Results: Imipramine in the dose used had no anxiolytic effect and no effect on motor activity. Selenium has anxiolytic effect in the plus maze and no effect on spontaneous motor activity. The anxiolytic effect of selenium disappeared when given with imipramine. Both imipramine and Selenium alone produced significant antidepressant effect in the forced swim test, this effect disappeared when selenium was administered with imipramine. Conclusion: Both the anxiolytic effect of selenium and the antidepressant effect of imipramine and selenium was abolished when administered together.